SAT0423 Understanding Delay in Diagnosis, Access to Care and Satisfaction with Care in Lupus: Findings from a Cross-Sectional Online Survey in the United States. (9th June 2015) - Al Sawah, S.; Daly, R.P.; Foster, S.; Naegeli, A.; Benjamin, K.; Doll, H.; Bond, G.; Moshkovich, O.; Alarcόn, G.
Abstract : Background: Early diagnosis is an area of great unmet need in lupus. This need and other aspects of care have been reported from a provider's perspective. Objectives: The aims of this survey were to understand the experience of patients with diagnostic delays and to assess their access to care and the extent to which their care needs are met. Methods: An online cross-sectional survey of English-speaking respondents aged ≥18 years with self-reported diagnosis of lupus was conducted across the US in partnership with the Lupus Foundation of America between February and March 2014. Demographic, clinical, and health-related quality of life information was collected, including a series of questions about patients' experiences with diagnostic delays, access to care, and healthcare resource use (HCRU). Satisfaction with care was measured using the LupusPRO care satisfaction scale 1, which has a score range of 0 to 100 (with 100 indicating the most satisfaction). Results: Of the 827 lupus respondents, 97.5% were females and 85.3% white. Lupus respondents took on average 2.1 years (standard deviation [SD], 4.9 years) to seek medical help from the time they first noticed lupus symptoms (95% confidence interval [CI], 1.8 to 2.5 years) and waited an average of 3.5 years (SD, 5.4 years) from the time they first sought medical help for their lupus symptoms until formal diagnosis (95% CI, 3.1 to 3.8 years). A total of 62.8% lupus respondents reported being misdiagnosed before receiving a formal diagnosis of lupus; 75% of them reported being misdiagnosed by a primary healthcare provider. The median number of providers lupus respondents visited before receiving a formal lupus diagnosis was 3 (range, 0-10+). Overall, the rate of HCRU among lupus respondents was relatively high, with fatigue being the most frequently reported cause for seeking out-patient care. Although 90.2% of lupus respondents had healthcare coverage, 21.9% (17.8% of those with coverage and 59.3% of those without) reported that they were unable to get all the prescription medication they needed to manage their lupus and 22.5% (17.4% of those with coverage and 69.1% of those without) reported that they were unable to get all the healthcare they needed including specialist care and hospitalization to treat their lupus. On the LupusPRO "satisfaction with care" domain, lupus respondents reported not being fully satisfied (mean, 61.6; SD, 31.4; 95% CI, 59.5 to 63.8). Conclusions: The results of this survey indicate a need to address the patients' reported delays and inaccuracies in medical diagnosis, the quality of care, and the access to appropriate medical services for patients with lupus. Increased awareness of lupus symptoms in the general community and clinician education to improve understanding of both diagnostic criteria and medical treatment options are necessary to reduce the burden of illness in lupus References: Jolly M, Pickard AS, Block JA, et al. Disease-specific patient reported outcome tools for systemic lupus erythematosus. Sem Arthritis Rheum 2012; 42: 56-65. Disclosure of Interest: S. Al Sawah Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, R. P. Daly: None declared, S. Foster Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. Naegeli Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, K. Benjamin: None declared, H. Doll: None declared, G. Bond: None declared, O. Moshkovich: None declared, G. Alarcόn: None declared